Exploring contextual differences for sexual role strain among transgender women and men who have sex with men in Lima, Peru - Satcher, Milan F. (2022)
Sexual and gender politics inform relational expectations surrounding sexual experiences of Peruvian transgender women (TW) and men who have sex with men (MSM). We used the framework of sexual role strain, or incongruence between preferred sexual role and actual sexual practices, to explore potential conflicts between personally articulated identities and externally defined norms of gender and sexuality and its potential to increase HIV/STI risk. Cross-sectional individual- and dyad-level data from 766 TW and MSM in Lima, Peru were used to assess the partnership contexts within which insertive anal intercourse was practiced despite receptive role preference (receptive role strain), and receptive anal intercourse practiced despite insertive role preference (insertive role strain). Sexual role strain for TW was more common with non-primary partners, while for MSM it occurred more frequently in the context of a primary partnership. Receptive role strain was more prevalent for TW with unknown HIV status (reference: without HIV) or pre-sex drug use (reference: no pre-sex drug use). For homosexual MSM, receptive role strain was more prevalent during condomless anal intercourse (reference: condom-protected) and with receptive or versatile partners (reference: insertive). Among heterosexual or bisexual MSM, insertive role strain was more prevalent with insertive or versatile partners (reference: receptive), and less prevalent with casual partners (reference: primary). Our findings suggest TW and MSM experience different vulnerabilities during sexual role negotiation with different partner-types. Future studies should explore the impact of sexual role strain on condom use agency, HIV/STI risk, and discordances between public and private presentations of gender and sexual orientation.